2006
DOI: 10.1523/jneurosci.4101-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3 Kinase Activation and AMPA Receptor Subunit Trafficking Underlie the Potentiation of Miniature EPSC Amplitudes Triggered by the Activation of L-Type Calcium Channels

Abstract: We have characterized a mechanism by which the amplitudes of miniature EPSCs (mEPSCs) in CA1 pyramidal neurons in rat hippocampal organotypic slice cultures are potentiated by approximately twofold after a series of depolarizing voltage pulses from -80 to ϩ20 mV. The increase in mEPSC amplitudes is triggered by the activation of L-type calcium channels and is independent of NMDA receptor (NMDAR) activation but also requires calcium release from intracellular stores. The potentiation induced by depolarizing pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…It has been shown that both induction and expression of LTP requires PI3K activity (Kelly and Lynch, 2000;Sanna et al, 2002;Opazo et al, 2003). PI3K is also physically associated with AMPARs and functionally coupled with AMPAR subunit trafficking during certain forms of plasticity, such as potentiation of mEPSC in response to activation of L-type calcium channels (Baxter and Wyllie, 2006) or synaptic NMDARs (Man et al, 2003). Multiple cellular processes can lead to activation of PI3K, such as activation of Src (Krymskaya et al, 2005), G-protein-coupled receptors (Shah et al, 2006), and Ca 2ϩ -calmodulin complex after NMDAR activation (Joyal et al, 1997;Man et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that both induction and expression of LTP requires PI3K activity (Kelly and Lynch, 2000;Sanna et al, 2002;Opazo et al, 2003). PI3K is also physically associated with AMPARs and functionally coupled with AMPAR subunit trafficking during certain forms of plasticity, such as potentiation of mEPSC in response to activation of L-type calcium channels (Baxter and Wyllie, 2006) or synaptic NMDARs (Man et al, 2003). Multiple cellular processes can lead to activation of PI3K, such as activation of Src (Krymskaya et al, 2005), G-protein-coupled receptors (Shah et al, 2006), and Ca 2ϩ -calmodulin complex after NMDAR activation (Joyal et al, 1997;Man et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, our results raise the possibility of a postsynaptic JAK2/PI3K-dependent mechanism for the inhibition of AMPAR-mediated synaptic transmission by leptin. However, PI3K activation causes AMPAR insertion (22,23), which should result in enhanced synaptic transmission. Such a mechanism would account for some leptin concentrations enhancing long-term synaptic plasticity at excitatory synapses (21,(38)(39)(40).…”
Section: Figurementioning
confidence: 99%
“…In addition, leptin enhances N-methyld-aspartate receptor (NMDAR) activity by activating PI3K and MAPK (15,20,21). Leptin-induced activation of PI3K may enhance AMPA receptor (AMPAR) synaptic transmission because PI3K increases the surface expression of AMPARs (22,23). Leptin also converts short-term potentiation (STP) into long-term potentiation (LTP) (21).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that tetanization with a very high frequency (200 Hz) or extracellular application of tetraethylammonium, a potassium channel blocker, can cause synaptic potentiation in a VDCCdependent manner (Grover and Teyler, 1990;Aniksztejn and Ben-Ari, 1991;Huang and Malenka, 1993); however, since these induction procedures were accompanied by synaptic stimulation, factors other than Ca 2ϩ might have contributed to these forms of LTP. Efforts to induce LTP with postsynaptic depolarization alone have not been so successful: in the visual cortex, application of intracellular tetanization was reported to induce either LTP or LTD, although it is unknown how these two forms of plasticity occur in the same condition (Volgushev et al, 1994), and in the hippocampus, there has been one report of mEPSC LTP in the culture system (Baxter and Wyllie, 2006); however, more physiological experiments with acute hippocampal slices have reported only short-term potentiation so far (Kullmann et al, 1992;Huang and Malenka, 1993;Chen et al, 1998). In this study, we found a condition in which LTP is induced by postsynaptic depolarization alone, using acute hippocampal slices from adult mice.…”
Section: Induction Of Non-hebbian Ltp By Postsynaptic Depolarizationmentioning
confidence: 99%